«C'est lui qui a ouvert la voie». La finale du prologue johannique - La Potterie, Ignace de (Biblica, 1988)
The verb έξηγήσατο in John 1,18 is still being discussed. For some its meaning is "explain" (Jesus was "the Father's exegete"); for others it means "reveal" ("He revealed him"). R. Robert rightly objected to these two interpretations and suggested seeing a conscious ambiguity in this word: it would mean both "He told about the Father" and "He led men to God". But this solution seems impossible since it gives the verb two different meanings simultaneously and presupposes an ellipsis which is never attested in St. John. However, Robert has the merit of drawing our attention to the first meaning of the verb. We continue this idea, while giving the full weight to the absolute use of έξηγήσατο. This construction is attested in all eras and implies precisely this first meaning: "to walk in front". The meaning of v. 186, therefore, is: "The only Son, who is back in the bosom of the Father, he is the one who has opened the way" (cf. the parallel at 14,6: he is "the Way" toward the Father). At the end of the article we show the importance of this exegesis, both for the understanding of the entire prologue and for the whole of the fourth gospel which it introduces.